Rehearsal Fundamentals - WEBER, Fred (Belwin Mills Publ., 1956)
Rehearsal fundamentals provides material in different sections, eachdealing with a different type of musical growth,such as tone & intonation, technic, rhytm, balance, and expression, thereby making possible concentrated study in whatever field the director thinks extra attention is advisable.